Prevention, susceptibility, and clinical features of coronavirus disease 2019 in postoperative patients (2020)
To the editor, The coronavirus disease 2019 (COVID-19) has rapidly spread worldwide and is now a global pandemic. Surgeries were curtailed in many hospitals during the pandemic, and the recommendation to delay all elective surgeries was issued in account of the increased mortality rate in peri-operative patients with COVID-19.